Relationship of Braille Reading Skills with Onset of Visually Impairment in Children with Visual Impairment in Mainstream Setting - Farida Shamim, Farhan Sarwar, Muhammad Asif Chaudhary (JIE, 2024)
The study was conducted to find out the relationship between Braille reading skill of children with visual impairment and onset of visual impairment in the context of Pakistan for which there were no studies as yet. The current study evaluated the Braille reading skill of children with visual impairment (both congenitally and acquired visually impaired) in Braille reading skill. Researcher scrutinizes the relationships among the braille reading skill and onset (age at loss of vision) on the basis of reading subtests. One hundred twenty-seven (127) boys and girls with visual impairment from different classes of five institutions of Lahore were the samples of this study. The students who contributed were registered in public and private special schools for blind children.